1998
DOI: 10.1172/jci893
|View full text |Cite
|
Sign up to set email alerts
|

T cells reactive to a single immunodominant self-restricted allopeptide induce skin graft rejection in mice.

Abstract: Alloreactive T lymphocytes can respond to foreign MHC complexed with foreign peptides through the direct pathway of allorecognition and can additionally recognize allopeptides expressed in the context of recipient (self) MHC through the indirect pathway. To better elucidate how indirect pathway-responsive CD4(+) T cells mediate allograft rejection, we isolated and characterized a TH1 T cell line from BALB/c recipients of B10.A skin that responds to a defined immunodominant, self-restricted allopeptide, I-Abeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…Moreover it allows comparison of each alloreactive pathway in a context where precursor frequency and repertoire are similar. In that context, our results confirmed previous studies that demonstrated that indirect recognition of a single immunodominant epitope can by itself initiate graft rejection [15,16]. However, they contrast with other studies showing that activation of alloreactive T cells in DLN or spleen follows similar kinetics [17,18].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover it allows comparison of each alloreactive pathway in a context where precursor frequency and repertoire are similar. In that context, our results confirmed previous studies that demonstrated that indirect recognition of a single immunodominant epitope can by itself initiate graft rejection [15,16]. However, they contrast with other studies showing that activation of alloreactive T cells in DLN or spleen follows similar kinetics [17,18].…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that in this model, anti-donor cytolytic activity mediated by CD8 ϩ T cells was thought to be the effector mechanism (22,23). Other lines of evidence have been provided suggesting that in the absence of a direct pathway, an indirect alloresponse is sufficient to ensure rejection of allografts (5,24). Valujskikh et al (24) have reported that reconstitution of SCID mice with a CD4…”
Section: R Ecognition By Recipient T Lymphocytes Of Alloantigens Exprmentioning
confidence: 94%
“…Other lines of evidence have been provided suggesting that in the absence of a direct pathway, an indirect alloresponse is sufficient to ensure rejection of allografts (5,24). Valujskikh et al (24) have reported that reconstitution of SCID mice with a CD4…”
Section: R Ecognition By Recipient T Lymphocytes Of Alloantigens Exprmentioning
confidence: 99%
“…The main obstacle resides in the difficulty of finding situations where indirect sensitization represents the only pathway available for activation of alloreactive T cells. The most convincing approaches that have been tried to date involve either the transplantation of MHC class II molecule-deficient organs or the adoptive transfer of in vitro-derived T cells sensitized by indirect recognition of allopeptides (6,13). Although elegantly designed, these experiments have major weaknesses.…”
mentioning
confidence: 99%